IMPLEMENTASI DANA PUNIA MENURUT AJARAN AGAMA HINDU - Sastrawan I Ketut Bali (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2017)
Hinduism has a doctrine that guides its people to always exist in the way of dharma in living life. Religious teachings that although very old, but still relevant to the development of the era. Kaliyuga said that the role of punia fund is very important in religious life. Dana punia is said to be the culmination of religious life. The Hindu scriptures teach that punia funds can not only be done with only the members of the treasures, but can also be done with a gift with a sincere heart and sincerity despite sacrificing feelings and punia in the form of gift in the form of body and soul. Dana punia also means giving to eliminate fear. Keywords: Implementation, Dana Punia, Hindu